Waste Management Challenges and Strategies in The City of Qom (International Journal of Applied Research in Management and Economics, 2018)
Recycling and planning of waste management is one of the strategic objectives of metropolitan areas in the field of biomedical management, which is important due to environmental issues and financial constraints of the municipalities and therefore the preparation of coherent recycling programs from the source and promotion of public awareness in Leading countries in developed countries have laid down coherent and clear rules on the management and management of wastes to ensure the effectiveness and effectiveness of waste management processes and practices. Based on this, the prevention of waste production and the reuse of urban waste (recycling) are considered essential to reduce waste management challenges and challenges. considering that the management of urban waste is one of the main issues and challenges for urban management, especially metropolitan, this paper tries to investigate and use theoretical foundations to the challenges of waste management in a case in Qom and suggestions and appropriate strategies are presented.